Human Capital Management Based on the Principles of Green Economy and the Creation of Green Jobs for Sustainable Territorial Development - RAKHIMZHANOVA, Gulmira; MAIDYROVA, Aigul; KOCHERBAEVA, Ainura (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).13, 2023)
As a result of the actualization of sustainable development and the strengthening of the role of green responsibility at all levels of the economy, there are significant changes in modern management practices to improve long-term economic, social, and environmental indicators of territorial development through the introduction of green technologies. The purpose of the study is to determine the possibilities of managing human capital based on the principles of a green economy and creating green jobs for sustainable territorial development in the Republic of Kazakhstan. Using the example of the Akmola region, Kazakhstan, quantitative indicators of green jobs in the fields of activity related to green technologies are determined, an expert survey is conducted, and a SWOT analysis of the strengths and weaknesses of creating green jobs in various sectors of the economy is carried out. It is concluded that green human capital management focuses on the introduction of environmentally friendly green technologies, forms the social foundation of high ecological awareness and proper skills of eco-innovation work of employees, and acts as a factor in the growth of sustainable territorial development.